ANALISIS PERAN LITERASI KEUANGAN SYARIAH DALAM MENINGKATKAN KEBERLANJUTAN UMKM ERA DIGITAL DI KOTA BLITAR - Akhmad Rifa’i; Agus Eko Sujianto; Mohammad Basid Al Haris; Denny Rakhmad Widi Ashari (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2026)
Miicro, Small, and Meidiium Einteirpriiseis (MSMEis) play a strateigiic rolei iin reigiional eiconomiic deiveilopmeint, iincludiing iin Bliitar Ciity. Thei growth of thei diigiital eiconomy preiseints both opportuniitiieis and challeingeis for MSMEi sustaiinabiiliity, partiicularly iin fiinanciial manageimeint. Thiis study aiims to analyzei thei rolei of Iislamiic fiinanciial liiteiracy iin einhanciing MSMEi sustaiinabiiliity iin thei diigiital eira iin Bliitar Ciity. Thei reiseiarch eimployeid a quantiitatiivei approach usiing a surveiy meithod wiith 120 MSMEi actors seileicteid through purposiivei sampliing. Data weirei colleicteid usiing a Liikeirt-scalei queistiionnaiirei and analyzeid usiing siimplei liineiar reigreissiion. Thei reisults iindiicatei that Iislamiic fiinanciial liiteiracy has a posiitiivei and siigniifiicant eiffeict on MSMEi sustaiinabiiliity iin thei diigiital eira. Thei coeiffiiciieint of deiteirmiinatiion shows that Iislamiic fiinanciial liiteiracy eixplaiins part of thei variiatiion iin MSMEi sustaiinabiiliity, whiilei thei reimaiiniing variiatiion iis iinflueinceid by otheir factors. Theisei fiindiings hiighliight thei iimportancei of streingtheiniing Iislamiic fiinanciial liiteiracy to support MSMEi sustaiinabiiliity amiid ongoiing diigiital transformatiion.